The impact of entrepreneurial capital on the performance of youth-owned enterprises in South Africa - Majola, Jwalane Elisa Pride (My University, 2017)
South Africa has one of the highest unemployment rates in the world, with youth unemployment sitting at 37.5 percent in 2016. In an attempt to remedy South Africa’s unemployment, the government sought entrepreneurship as a solution. The South African government has implemented various policies and established numerous institutional bodies to accelerate entrepreneurship. Some of these policies and bodies are aimed specifically at enhancing entrepreneurship among the youth. In order to understand the best approach to assist these young entrepreneurs, it is important to understand what drives performance in current young entrepreneurs’ enterprises. This paper evaluated the impact that entrepreneurial capital (human, social, and financial capital) had on the performance of youth-owned enterprises. It surveyed 199 young entrepreneurs (between 18 and 35 years old) to understand what drives performance within their enterprises. The research found that there were high levels of performance within youth-owned enterprises, when there were high levels of human capital and social capital. However, there was a negative relationship between financial capital and the performance of youth-owned enterprises. Overall, the research concluded that high levels of entrepreneurial capital had a positive relationship with the performance of youth-owned enterprises. The objective of this study was to understand what drives the performance of youth-owned enterprises, in order to best facilitate government assistance and support for young entrepreneurs. The outcome suggests that human capital and social capital drive performance of youth-owned enterprises, it would thus be advisable for the South African government to focus on those two variables when drafting policies and forming institutional bodies to enhance youth entrepreneurship.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management specialising in Entrepreneurship and New Venture Creation. Johannesburg, 2017
Keywords: Youth--Employment--South Africa; Unemployment--South Africa; Entrepreneurship--South Africa; Youth--Social networks--South Africa